The Archaic words of Minangkabaunese found in Padang Lua - Fauzan Azim; Jufrizal Jufrizal (Universitas Negeri Padang, 2020)
The aim of this study is to figure out what are the archaic words of Minangkabaunese language found in Padang_Lua sub-dialect. Type of this research is descriptive qualitative in order to describe what are the causes of the extinction in certain words. This research successfully figured out that there are thirty one percents of archaic words found in Padang Lua sub-dialect by using a hundred words of Minangkabaunese language which are potentially become the archaic words. The factors of archaic words in Padang Lua sub-dialect caused by migration, bilingualism, intervention of Indonesian language, decreasing number of old generations, inter marriage, and technological developments. The main factor that contributes dominantly, the first is intervention of Indonesian language and the second is migration. Thus, it can be concluded that intervention of Indonesian language take an important role in causing words into archaic words.